2016
DOI: 10.1002/stem.2320
|View full text |Cite
|
Sign up to set email alerts
|

IGF/STAT3/NANOG/Slug Signaling Axis Simultaneously Controls Epithelial-Mesenchymal Transition and Stemness Maintenance in Colorectal Cancer

Abstract: Discovery of epithelial-mesenchymal transition (EMT) and cancer stem cells (CSCs) are two milestones in people exploring the nature of malignant tumor in recent decades. Although some studies have presented the potential connections between them, the link details, underneath their superficial correlation, are largely unknown. In this study, we identified a small subpopulation of NANOG-positive colorectal cancer (CRC) cells, and demonstrated that they exhibited characteristics of CSCs and EMT traits simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 40 publications
3
73
0
Order By: Relevance
“…Once the cancer cells obtain mesenchymal phenotypes, they gain the ability to migrate into the stroma or migrate to distant sites and organs, and finally contribute to tumor metastasis and recurrence [42,43]. In addition, numerous studies have also indicated that cancer cells undergoing EMT attain certain characteristics of cancer stem cells, which leads to chemo/radio resistance and tumor immune escape [44]. It is noteworthy that PD-L1 has been considered as an important mediator of EMT in certain human cancer tissues, such as lung cancer, colorectal cancer, and head and neck cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Once the cancer cells obtain mesenchymal phenotypes, they gain the ability to migrate into the stroma or migrate to distant sites and organs, and finally contribute to tumor metastasis and recurrence [42,43]. In addition, numerous studies have also indicated that cancer cells undergoing EMT attain certain characteristics of cancer stem cells, which leads to chemo/radio resistance and tumor immune escape [44]. It is noteworthy that PD-L1 has been considered as an important mediator of EMT in certain human cancer tissues, such as lung cancer, colorectal cancer, and head and neck cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is the primary cause of mortality in patients with CRC, the mechanism of which remains to be fully elucidated (3,18). Further investigation into the underlying mechanisms of CRC metastasis is required.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming is one of the key features of cancer cells (18). SREBP1 has become an area of interest in cancer biology because it is a key regulator of lipid metabolism (19).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with gain-of-function (GOF) mutations in STAT3 shape the cancer gene expression landscape of inflammatory liver adenomas or of mature T cell neoplasia (26,27). Importantly, STAT3 regulates also stem cell to tissue fate and invasive processes through epithelial to mesenchymal transitions or mesenchymal to epithelial transitions during embryo or cancer progression (28). Thus, STAT3 can control key differentiation processes under physiologic or malignant conditions.…”
Section: Stat1/3 Signalling In Tumour Biologymentioning
confidence: 99%